Beyond The Bustle: Fashion As A Vehicle For Female Empowerment In Louisa May Alcott’s “An Old-Fashioned Girl” (Journal of Namibian Studies : History Politics Culture, 2023)
Fashion emerges as a powerful metaphor in Louisa May Alcott’s An Old-Fashioned Girl to represent the intricate interaction between social expectations and individual autonomy for women in Victorian America. Within the framework of Alcott’s story, this study explored the role of dress in empowering women. During the Victorian period, there were significant changes in societal standards and gender roles due to events such as the American Civil War, the Second Industrial Revolution, and the Women’s Suffrage Movement. This article examines how clothing choices in Little Women by Louisa May Alcott convey and challenge the dominant ideals of virtue and femininity through a study of her depiction of fashion. Polly Milton, the heroine of Little Women by Louisa May Alcott, experiences the sartorial environment of her era via the power of clothing to express who she is and what she stands for. As women’s duties grew outside their homes, clothing became a means of expressing and navigating these changes. This dissertation delves into the intricate connection between clothing, Victorian-era social norms, and women’s empowerment by exploring how Polly’s wardrobe choices align with her journey towards self-determination and personal development. In the end, An Old-Fashioned Girl provides a fascinating perspective from which to examine how femininity changes over time, and how dress remains a cultural and political touchstone.